A comparative study on geographic‐based routing algorithms for flying ad‐hoc networks. (4th March 2021) - Agrawal, Juhi; Kapoor, Monit
Summary: The advancement of the technology and broad availability of low‐cost devices (e.g., networking technology, micro‐embedded computers, and sensors, etc.) have opened new ways for the expansion of flying ad‐hoc networks (FANETs). The unmanned aerial vehicles (UAVs) have the potential to change their trajectory freely in the case of FANETs. This freedom demands efficient routing to make the network connection smooth. However, designing routing protocols for FANETs is a crucial task for highly dynamic nodes like UAVs. The position‐based routing demonstrated high efficiency and resilience to handle the high mobility of UAV nodes in FANETs as compared to topology‐based routing protocols. Geographic routing protocols utilize the coordinates of the node to greedily proceed toward the destination. This article presents an extensive review of position‐based or geographic routing protocols in FANETs. Previous survey papers have performed a comparative analysis of all the protocols on different network conditions, assumptions, tools, and settings, therefore their performance is not comparable. The novelty of this survey is that this article performs the comparative analysis of various geographic routing protocols by evaluating all the geographic routing protocols over a common network scenario with a varying number of nodes. The starting phase of this article covers the basic outline of FANETs. Thereafter, an absolute study of the geographic based routing protocol has been presented by distinguishing the routing protocols on the basis of path and packet forwarding strategy. This article further emphasizes on the strength, weaknesses, quality of service (QoS), and comparative analysis of the various characteristics of the geographic routing protocols. Finally, a performance comparison summary of all the analyzed routing protocols for FANETs has been presented. The open research issues have been discussed at the end of this article.